Dietary knowledge, attitude, and practice regarding prevention of iron deficiency anemia among pregnant women in Riyadh, Saudi Arabia - Ayidh Alosaimi, Ashwaq; Abdullah Alamri, Sabreen; Mohammed Abduljawad, Manal; Mohammed Yakout, Sahar; Abdelatty Moawed, Salma (International Journal of Advanced Nursing Studies, 2020)
Background: Iron deficiency anemia (IDA) is recognized as the world’s most widespread nutritional disorder, affecting 1.6 billion people that constitute about 25% of the global population, and it is one of the most common diseases complicating antenatal women worldwide, particularly in the developing countries. There have been few research studies on IDA in pregnancy in Arab countries including Saudi Arabia.Objectives: This study aimed to assess the knowledge, attitude, and practice (KAP) on IDA among pregnant women in Riyadh, Saudi Arabia.Methods: A correlational study was used to collect data from a convenience sample of 314 pregnant women in Al Yammamah Hospital. Socio-demographic and obstetric characteristics, knowledge, attitude, and practice toward IDA during pregnancy questionnaire were determined and were analyzed for association. The KAP questionnaire was developed by the researchers based on Food and Agriculture Organization (FAO) guidelines.Results: Majority of the participants were in the age group 31 years and older who were university graduates, housewives, and have a monthly income of more than 5000 Saudi Riyals. In addition to their obstetric history, majorities were multigravida and multipara, in their third trimester, had no previous surgical or obstetric surgical history or complications in their previous pregnancies. Significant associations were found between the level of hemoglobin and income and dietary practices. Education is a major predictor of knowledge, attitude and practice among Saudi pregnant women.Conclusions: Saudi pregnant women have modest knowledge and positive attitude regarding IDA during pregnancy. Appropriate nutritional counseling during antenatal follow up should be encouraged and should include all women in reproductive age.